2017
DOI: 10.1371/journal.pone.0173119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating lung cancer screening in China: Implications for eligibility criteria design from a microsimulation modeling approach

Abstract: More than half of males in China are current smokers and evidence from western countries tells us that an unprecedented number of smoking-attributable deaths will occur as the Chinese population ages. We used the China Lung Cancer Policy Model (LCPM) to simulate effects of computed tomography (CT)-based lung cancer screening in China, comparing the impact of a screening guideline published in 2015 by a Chinese expert group to a version developed for the United States by the U.S. Centers for Medicare & Medicaid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…[13] If implemented in China with full adherence, these screening guidelines would prevent about 20,000 (2.9%) more lung cancer deaths in China through 2050 than the CMS guidelines would, but at a price of about 445 million (44.7%) more screens. [40] A combination of tobacco control programs and a lung cancer screening guideline fitted to the population would likely be most effective in China, as is corroborated by our previous study reporting a greater mortality reduction rate if smoking cessation interventions were added to an annual lung cancer screening program in the United States. [34]…”
Section: Discussionmentioning
confidence: 56%
“…[13] If implemented in China with full adherence, these screening guidelines would prevent about 20,000 (2.9%) more lung cancer deaths in China through 2050 than the CMS guidelines would, but at a price of about 445 million (44.7%) more screens. [40] A combination of tobacco control programs and a lung cancer screening guideline fitted to the population would likely be most effective in China, as is corroborated by our previous study reporting a greater mortality reduction rate if smoking cessation interventions were added to an annual lung cancer screening program in the United States. [34]…”
Section: Discussionmentioning
confidence: 56%
“…Although statistical significance was not achieved because of the small sample size, the results showed a 17% reduction in overall mortality and a 30% reduction in lung cancer-specific mortality with LDCT. Two simulation studies that favored LDCT screening in China were also published this year, and similar conclusions were reached, although different models and parameters were used [ 3 , 4 ].…”
mentioning
confidence: 87%
“…A major conclusion of the two recent studies [ 3 , 4 ] on lung cancer screening in China was the emphasis on deliberately selecting candidates for screening. According to a study published by Katki et al [ 11 ] in 2016, several screening effectiveness and efficiency metrics (e.g., number needed to screen to prevent one lung cancer death) could be optimized in the US with a “risk-based approach” for selecting the high-risk population.…”
Section: Study Area 1: Quantitative Analysis-based Population Screenimentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion criteria for screening have a major impact on cost-effectiveness 122 . For example, micro-simulation models comparing the use of the Chinese guidelines with those of the US Centers of Medicare and Medicaid Services concluded that the application of local recommendations would result in 50% improvement in mortality reduction in females (2.79% versus 1.97%), saving an additional 20,000 lives in China by 2050, but only if almost 50% more screenings were performed 123 . In such cases, RPM utilization could optimize screening eligibility and effectiveness, possibly resulting in a substantial reduction in budget impact and making LDCT screening eventually cost-saving if non-curative treatment costs continue to rise 97 .…”
mentioning
confidence: 99%